Pengembangan Media Kartu Pantun untuk Meningkatkan Kemampuan Menulis Pantun Siswa Kelas VII SMP Negeri 4 Percut Sei Tuan - Annisa Azzahra; Rina Devianty; Edi Saputra (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2025)
The research entitled "Development of Pantun Card Media to Improve Pantun Writing Skills of Grade VII Students of SMP Negeri 4 Percut Sei Tuan" was motivated by the low ability of students in writing pantun due to a lack of understanding of pantun structure and limited interesting learning media. The method used is Research and Development (R&D) with the ADDIE development model through the stages of analysis, design, development, implementation, and evaluation. Data were obtained through validation by media experts, material experts, and language experts, teacher and student response questionnaires, and pretest and posttest tests in the experimental and control classes. The validation results showed that the pantun card media was included in the "very valid" category with a percentage score of 92% from media experts, 92% from language experts, and 100% from material experts with an average of 94.67%, as well as practicality tests by teachers of 92% and 89.85% from students which indicated that this media was very suitable for use and well received. The effectiveness test showed a significant increase in the ability to write pantun in the experimental class compared to the control class with an N-Gain score of 57.83%, so that the pantun card media is quite effective to be used as an innovative alternative in learning Indonesian, especially the material for writing pantun.